PENGARUH PENERAPAN SISTEM AKUNTANSI BERBASIS KOMPUTER TERHADAP COST REDUCTION DAN DECISION MAKING PADA UKM DI KOTA SEMARANG - Chrysvina Florencia Shirleen Prayogo; Dwi Ratmono (Diponegoro Journal of Accounting, 2022)
Small and Medium Enterprises (SMEs) are one of the important sectors that play a role in economic development in Indonesia, so empowering SMEs in Indonesia is very strategic. Computer-based accounting systems can assist SMEs in recording accounting and financial reports in a systematic and fast manner. There has been no further research on the benefits of computer-based accounting systems in cost reduction and effective decision making directly. Therefore, this study will examine the direct effect of implementing a computer-based accounting system on cost reduction and decision making in SMEs in Semarang City.Data collection was carried out using a questionnaire that was distributed directly and online via a google form link. The preliminary research was conducted by distributing questionnaires to 30 SMEs in Semarang City for a pretest in testing the validity and reliability of the constructs, then continued distributing it to 120 SMEs in Semarang City, and 98 SMEs participated. The data were statistically processed using SPSS in the non-response bias test and the outer and inner models were tested using the PLS-SEM method.Based on the test results of the PLS-SEM outer model, it was concluded that the variables of computer-based accounting system, cost reduction, and decision making in this study were declared valid and reliable. The test results of the PLS-SEM inner model state that the two research hypotheses are accepted. The first hypothesis, computer-based accounting system has a positive effect on cost reduction in SMEs in Semarang City is accepted. The second hypothesis, computer-based accounting system has a positive effect on decision making in SMEs in Semarang City is accepted.